Data Aggregation and Routing Guidance with QoS Guarantee in VANETs - Cheng Feng; Zhijun Li; Shouxu Jiang; Rui Zhang (International Journal of Distributed Sensor Networks)
Data aggregation is a useful technology that can decrease the communication bandwidth cost in the process of data gathering in VANETs. However, data aggregation may lose some data accuracy. Current data aggregation schemes in VANETs only consider saving bandwidth cost while ignoring the application requirement, which may result in the inaccuracy of aggregated data for dynamic routing application. Therefore, we propose a framework in which application demands are considered in the process of data aggregation to ensure the accuracy of aggregated data for dynamic routing application. The framework consists of three parts: extracting QoI constraints of aggregated data, distributing the QoI-based data gathering queries, routing and aggregating data with QoI constraints. First, we propose average allocation method to handle the demand of single user and utilize convex optimization to handle multiuser demands. Then, we distribute the QUERY message with QoI constraints in the interested area. Last, we propose QoI-DG protocol to do two kinds of data aggregation operation, namely, AVERAGE aggregation and HISTOGRAM aggregation. Simulation experiments show that our proposed method can increase about 20 percent in the collected data rate and save 15 percent communication bandwidth cost in the process of data gathering in VANETs.